Relationship between Cost Leadership Strategy and Organizational Performance of Kilimanjaro International Leather Industries Company Limited, Tanzania - Kanju, Robert N.; Isanzu, Janeth (PAN-AFRICAN JOURNAL OF BUSINESS MANAGEMENT, 2023)
Due to increased competition which is brought about by liberalization and deregulation, organizations are faced with greater demands to be flexible, responsive and efficient in order to be more competitive. As a result of this, organizations are faced with a lot of challenges in their effort to remain competitive in the market. This study intended to probe the relationship between cost leadership strategy and organizational performance at Kilimanjaro International Leather Industries Company Limited in Moshi Municipal, Tanzania as the case study. In doing this, the study adopted quantitative research design. The sample size for this study was 353 out of 3000 total employees, managers and corporate clients at Kilimanjaro International Leather Industries Company Limited. Simple random sampling technique was custom made within the choice of key informants. The coded data was examined by using descriptive statistics and regression analysis where an alternative hypothesis was accepted. This was completed with the aid of statistical package for social sciences version 20. Therefore, findings vindicated that cost leadership strategy plays significant role in deciding organizational performance. The study concludes that cost leadership strategy has direct relationship to organizational performances. Based on the findings, the study recommended that the manufacturing firms adopt cost leadership strategy as it had been found to have a positive significant effect on performance.